(untitled) (Journal of the Medical College for Women & Hospital, 2024)
Sub acute sclerosing panencephalitis (SSPE) is a neurodegenerative disease of the central nervous system (CNS) caused by defective measles virus infection. There are many criteria developed to diagnose SSPE, one of them is Dyken criteria. The SSPE diagnosis is based on characteristic clinical symptoms: intellectual deterioration, behavioral changes, poor school performance, frequent fall; EEG findings: burst suppression pattern in myoclonic phase and in cerebrospinal fluid (CSF) there is findings of elevated antibody titres against measles. Here we present a case who fulfill most of the Dyken criteria: Repeated fall during walking, poor school performance, jerky movement of body. EEG (electroencephalograph) findings: interictal expression of localization related epilepsy with focal neuronal dysfunction at both hemispheres with pseudo periodic pattern, could be very early stage of encephalopathy, such as SSPE. In CSF the total IgG was 11.64 mg/dl, measles antibody IgM serum was found to be positive :1.208. There is no cure of SSPE. Few percentage may recover spontaneously. Isoprinosine with or without interferon alpha, ribavirin, IVIG (intravenous immunoglobulin) may be given for slowing the course of disease. Sodium valproate, carbamazepine may be given for control of myoclonic seizure. We managed the patient by sodium valproate for control of myoclonic seizure and advised isoprinosine for slowing the progression of disease. J Med Coll Women Hosp. 2024; 20 (1): 76-80